Development of the Singgalang Newspaper 2007-2020 - Jayanti, Kurnia Rahmadina; Erawati, Meri; Junaidi, Juliandry Kurniawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
The aim of this research is to find out why Singgalang is digitizing. To find out the challenges and strategies of the Singgalang publisher. The research method uses heuristic methods, source criticism, interpretation, historiography. From the results of the research that has been carried out, it can be concluded that Singgalang has made many changes both physically (newspapers) and digitally. The reasons for these changes are based on reader comfort, maintaining existence and keeping up with current developments.  In the early 2000s, Singgalang converged by changing the appearance of the newspaper in terms of shape and size, changing it to a color newspaper, and increasing the number of photos. Then in 2007, Singgalang digitized it by creating the website singgalang.co.id.